The Impact of Direct Cash Transfers (BLT) and Non-Cash Transfers (BNT) on Poor Households in Rokan Hulu District - Khairini Rini; Dahlan Tampubolon; Rita Yani Iyan (Universitas Bangka Belitung, 2023)
This study aims to determine how the impact and differences of Direct Cash Assistance (BLT) and Non-Cash Assistance (BNT) on Poor Households in Rokan Hulu Regency. The method used in this research non probability sampling with number of samples as many as 80 poor household respondents who received Direct Cash Assistance (BLT) and Non-Cash Assistance (BNT). The data used in this research are primary data and secondary data. The data analysis method used was descriptive qualitative analysis and the Independent Sample T-test. The results of this study indicate that Direct Cash Assistance (BLT) and Non-Cash Assistance (BNT) have an impact on poor households in the Ujung Batu sub-district. Poor Households in the Ujung Batu sub-district of Rokan Hulu district and there is a difference between poor households that receive Direct Cash Assistance (BLT) and Non-Cash Assistance (BNT).